Correlation between emotion regulation and mental well-being among university students during COVID-19 - Mohd Shah, Nur Syahirah; Ahmad Basri, Nadzirah; Ibrahim, Muhammad Ariff; Nik Hashim, Nik Nur Wahidah; , (Universiti Kebangsaan Malaysia, 2022)
Studies have shown that emotion regulation has a significant association with mental health. It also serves as protective factor against mental illness. This current study intends to examine how emotion regulation contributes to mental well-being of university student especially in the pandemic. A cross-sectional study conducted among 478 university students (221 medical and257 non-medical students) were selected using convenience sampling method. Data were collected using Emotion Regulation Questionnaire (ERQ) and Short Warwick-Edinburgh Mental Well-being Scale (SWEMBS). T-test, Pearson correlation and linear regression using SPSS version 25 were used to analyse the data. There was a significant difference between mental well-being and expressive suppression strategy (subscale of ERQ) between medical and non-medical students respectively (p<0.003, p<0.01). A significant positive correlation was established between cognitive reappraisal (subscale of ERQ) and mental well-being with the value of (r=0.45, p<0.001), while expressive suppression showed no significant correlation. Regression analysis indicated that cognitive reappraisal could predict the mental well-being of university students (B=2.11, p<0.001). Emotion regulation has been found to be associated with mental well-being of university students especially in the subscale of Cognitive Reappraisal. Cognitive reappraisal has been found to predict mental well-being of students which shows that by changing the way one thinks about a life situation, it may help them to improve their mental well-being.